Bio-inspired synthetic approaches: from hierarchical, hybrid supramolecular assemblies to CaCO3-based microspheres. Issue 19 (4th May 2017) - Marzec, Bartosz; Zhang, Lei; Zhu, Nianyong; Schmitt, Wolfgang
Abstract : A bio-inspired synthetic approach to Ca(ii )-based coordination assemblies is reported; the supramolecular system was used as habit modifier for CaCO3 materials. Abstract : A bio-inspired synthetic approach to unprecedented hybrid supramolecular assemblies [Ca(Me2 hda)(H2 O)3 ]·H2 O (1 ) and [Ca(C12 hda)(H2 O)2 ]·H2 O (2 ), that are stabilized by iminodiacetate-substituted organic ligands is reported. The results of the single-crystal X-ray analysis of1 further allowed the use of electron microscopy to verify the supramolecular structure of the fibrous assemblies of2 that incorporate extended alkyl-substituted ligand derivatives.2 reveals interesting features that distinguish these soft structures from purely inorganic, brittle materials: meshes of nanobelts transform on solid supports to form homogeneous films covering extended, micro-sized areas. The use of the reported ligand system as a habit modifier for CaCO3 results in hierarchical calcite aggregates. The structure-influencing effects of the ligands and their supramolecular assemblies promote the formation of calcite disks that tessellate into hollow microspheres that contain distinctive openings.